2017
DOI: 10.3389/fcimb.2017.00178
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia chaffeensis Tandem Repeat Effector Targets Differentially Influence Infection

Abstract: Ehrlichia chaffeensis infects mononuclear phagocytes and survives intracellularly by exploiting host cell processes to evade host defenses. The mechanisms involved are not fully defined, but appear to rely largely on a subset of tandem repeat proteins (TRP) effectors. E. chaffeensis TRPs are type 1 secreted effectors that interact with a functionally diverse group of host cell targets associated with various biological processes. In this study, we investigated the influence of TRP host target proteins on ehrli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Quantification of E. chaffeensis by qPCR. E. chaffeensis infection was evaluated by real-time qPCR as previously described (25). Briefly, E. chaffeensis-infected THP-1 cells (48 hpi) were pelleted, washed with PBS, and lysed in SideStep lysis and stabilization buffer (Agilent, Santa Clara, CA) at room temperature, and lysates were used in qPCRs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of E. chaffeensis by qPCR. E. chaffeensis infection was evaluated by real-time qPCR as previously described (25). Briefly, E. chaffeensis-infected THP-1 cells (48 hpi) were pelleted, washed with PBS, and lysed in SideStep lysis and stabilization buffer (Agilent, Santa Clara, CA) at room temperature, and lysates were used in qPCRs.…”
Section: Methodsmentioning
confidence: 99%
“…Based on sequence similarity and position within the cluster, mammalian Hox genes have been assigned to 13 paralogous groups, and each cluster has 9 to 11 members (24). E. chaffeensis TRP120 interacts with the PCGF component of PRC1, and a previous study demonstrated that knockdown of PCGF5 enhances ehrlichial infection (25). Thus, we investigated the functional relevance of this interaction to better understand the role of PcGs and PRC-associated functions during E. chaffeensis infection.…”
mentioning
confidence: 99%
“…Our Y2H data also identified some closely related or function-associated interacting partners of E. chaffeensis TRPs, including a member of solute carrier family, solute carrier family 4 member 7 (SLC4A7). We previously identified solute carrier family 2 member 3 (SLC2A3) interacting with TRP120, solute carrier family 25 member 42 (SLC25A42) and family 46 member 3 (SLC46A3) interacting with TRP47, and solute carrier family 43 member 3 (SLC43A3) interacting with TRP32 ( 12 , 13 , 23 ). The solute carrier (SLC) consists of a large series of membrane transport proteins, including 52 families and over 400 members identified so far.…”
Section: Discussionmentioning
confidence: 99%
“…TRP120 interacts with intercellular adhesion molecule 3 (ICAM3) ( 12 ), which promotes drug resistance via inhibition of apoptosis, and with protein phosphatase 3 regulatory subunit B alpha (PPP3R1), which positively regulates TNF-related apoptosis ( 41 , 42 ). Moreover, TRP32, TRP47, and TRP120 interact with a wide range of immunoglobulins and ribosomal proteins, such as IGL, IGKC, IGHA1, IGHV, IGLL1, IGLL5, RPL24, and RPL11 ( 12 , 13 , 23 ), which are associated with stabilization of antiapoptotic protein expression and p53-mediated apoptosis, respectively ( 43 , 44 ). Most of TRP75 target proteins involved in apoptosis exhibited strong interactions with TRP75 by coimmunoprecipitation and immunofluorescence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…TRPs are immunoreactive proteins that contain protective linear antibody epitopes in the tandem repeat (TR) domains. In addition, previous studies have demonstrated that TRP effectors interact with a diverse array of host proteins involved in biological processes such as cell signaling, intracellular transport, metabolism, protein post-translational modification, apoptosis, and regulation of transcription [ 2 ]. Notably, E .…”
Section: Introductionmentioning
confidence: 99%